Casa e Caixilho - equação e seleção no projeto de arquitetura para uma habitação unifamiliar - Paulo José Ferreira Topa (2018)
The theme of this Dissertation, CASA and CAIXILHO, results from an in-depth and thoughtful analysis of the differentand very varied technical possibilities that, at present, the scope of fenestration presents, when used in the design ofa single-family dwelling. The selection of the theme fell on the result of the equation between the House and theFrame.At an early stage, my thinking was centered on the project carried out some time ago, a project entitled A-Ver-o-Marwhen the need arose to make profound changes to the architecture project developed, proposed by the client.The request to change the project arrived at the final moment of my academic journey. Therefore, the opportunityto analyze what he had projected before being a student of the Faculty of Architecture of the University of Porto and,with another look, project again in very different circumstances.As for me, the frequency of the Architecture course had a fundamental importance in my life and the way I now seeArchitecture, it was felt the need to expose the way in which it was, within the academic course, to design a house ofthe Gardener - now as a student of FAUP.His long experience as technical director of works, in the period immediately preceding my admission as a student ofthe Faculty of Architecture of the University of Porto, granted a broad knowledge of the technical aspects of the work,but also a wide understanding about the materials used in the works. Including this scope in this dissertation madeperfect sense. Therefore, the idea underlying the development of the work was the search for the differentiatedrelationship between design and construction in three essential moments: as an architect without a degree, as astudent of the Architecture course and as a licensed architect.Thus, the present dissertation tries to leave the testimony of the importance of the knowledge to find depth in theindividual production of each one.After the course, there is, first of all, a greater demand, a greater rigor, a greater capacity to interrelate knowledge inthe realm of the domestic space project, and the emerging technical issues that consolidate the quality of living.As a construction director, the strictly technical question was completely dominated. However, now, after theacademic course, I realized that the question of the constructive way implies the architectural form and thisrelationship is essential to achieve the quality of the work. Otherwise, I can now say, it is not architecture.